2016
DOI: 10.1113/ep085367
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in vascular endothelial function and health in humans: impacts of exercise

Abstract: New Findings r What is the topic of this review?This brief review discusses potential sex differences in arterial function across the age span, with special emphasis on the effects of oestrogen and testosterone on the vascular endothelium. r What advances does it highlight?We discuss the relationship between the impacts of sex hormones on arterial function and health in the context of epidemiological evidence pertaining to the menopause and ageing. Studies performed in humans are emphasized, alongside insights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 74 publications
(77 reference statements)
1
49
0
Order By: Relevance
“…This proposal requires further investigation and the situation may be different in healthy subjects and those with elevated sympathetic drive a priori (Roveda et al 2003;Carter and Ray 2015). It is also now clear that important differences in autonomic function may result from differences in receptor density and function that exist between men and women of different ages (Green et al 2015;Joyner et al 2015).…”
Section: Some Things We Do Not Know About Exercise Training and Artermentioning
confidence: 99%
“…This proposal requires further investigation and the situation may be different in healthy subjects and those with elevated sympathetic drive a priori (Roveda et al 2003;Carter and Ray 2015). It is also now clear that important differences in autonomic function may result from differences in receptor density and function that exist between men and women of different ages (Green et al 2015;Joyner et al 2015).…”
Section: Some Things We Do Not Know About Exercise Training and Artermentioning
confidence: 99%
“…To control for the effect of changes in circulating hormones on vascular function, all women were assessed within the first 7 days of the follicular phase of the menstrual cycle. 20 The study was approved by the University of Western Australia's Human Research Ethics Committee and conformed to the standards outlined in the Declaration of Helsinki. Participants were informed of all experimental procedures and any potential associated risks.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…Although it is not completely clear why this same association was not observed among the female officers, there are a few possible reasons. Estrogen levels have been shown to be directly associated with better endothelial function [Teede ; Green et al, ]. One study showed that FMD declined in men at an earlier age than in women and that menopause was correlated with a steep FMD decline [Celermajer et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Fewer women in this cohort work on the night shift compared with men. Also, levels of male and female sex hormones may impact the vasculature [Green et al, ]. Therefore, a secondary objective was to determine if gender significantly modified the relationship between shiftwork and change in endothelial function.…”
Section: Introductionmentioning
confidence: 99%